Quantum Chemical Calculations on Two Compounds of Proquazone and Proquazone Type Calcites as a Calcium Sensing Receptor (CaSR) Inhibitory Profiles - Ahmed Hassen Shntaif; Rashi, Zahraa M.; Al-Sawaff, Zaid H.; Kandemirli, Fatma (Pleiades Publishing Ltd, 2021)
A quantum chemical study was done on two compounds of proquazone and proquazone type calcilytics (6-methoxy-1-(propan-2-yl)-4-[4-(propan-2-yl)phenyl]-1,2 dihydroquinazolin-2-one), and (1-{[3-(2-hydroxyethoxy)phenyl]methyl}-6-(prop-2-yn-1-yloxy)-5-[3-(propan-2-yl)phenyl]-1,2-dihydroquinazolin-2-ol), as a calcium-sensing receptor. The study was done in gas phase using DFT/B3LYP method was considered to calculate the energetic behavior and the quantum chemical descriptors such as the energy gap between HOMO and LUMO, the total energy for various orbital transitions, chemical hardness, softness, electrophilicity index, electro-negativity. Besides, a theoretical study was done on the compounds, in order to study and examine the effect of changing the temperature of the molecule which was from (200 to 1000 K) on thermodynamics properties (enthalpy, entropy, heat capacity, and correlation properties). From the results obtained, there was a noticeable difference between the two compounds regarding the chemical parameters, where the first compound seems to be more stable than the second compound.
Keywords: 3. Good health